A-07 Initial Symptoms, Pre-Existing Emotional Factors, and Symptoms of Stress During Recovery from Concussion. (13th July 2022) - Bunt, S; Didehbani, N; Stokes, M; Miller, S; Bell, K; Cullum, C M
Abstract: Purpose: Investigate the association of initial symptoms, mechanism of concussion, and emotional state with symptoms of stress reported during recovery from concussion in high school students. Methods: Concussed High School students (n = 183) aged 13–18 were evaluated within 30 days of injury at a North Texas Concussion Registry (ConTex) clinic with 71% (n = 130) sport-related. Subjects completed a medical history, the Sport Concussion Assessment Tool-5 Symptom Evaluation (PCSS), General Anxiety Disorder (GAD-7), and Patient Health Questionnaire-8 (PHQ-8) at initial visit. At three-month follow-up subjects completed the PTSD Checklist for DSM-5 (PCL-5). A linear regression was conducted predicting total scores on the follow up PCL-5. Predictors included initial Total PCSS Symptom Score, GAD-7, PHQ-8, sex, mechanism of injury (sport vs non-sport) and history of treatment for anxiety/depression. Results: A multiple regression model predicting participant's total PCL-5 score at three month follow-up (R 2 = 0.40, p < 0.001) included PHQ-8 (β = 0.34, p < 0.001), GAD-7 (β = 0.20, p = 0.016), history of treatment for depression (β = 0.17, p = 0.015), severity of initial symptoms (β = 0.15, p = 0.045) and mechanism of injury (β = −0.14, p = 0.018). There was no significant difference in PCL-5 scores between sport vs non-sport injury groups. Conclusions: Pre-existing depression and higher levels of self-reported anxiety and/or depression at time of injury may be associated with increased symptoms of stress during concussion recovery. Severity of initial symptoms and mechanism of injury may also be related to feelings of stress during recovery. Further investigations should include baseline measure of stress prior to injury.